Design of an FPGA-Based OFDM Transceiver for DVB-T Standard - Gopal, Lenin; Tze, D.; Ishak, N. (IEEE Press, 2011)
The current communication systems tend to use OFDM systems in order to provide high data rates, minimize inter symbol interference and fading effect. Some examples are 802.11, 802.16, MC-CDMA, Digital Video Broadcasting (DVB), Wireless USB or Wireless Firmware among others. Trying to provide a solution to the new devices emerging, slow standard adoption, poor spectrum use, etc. This work presents an FPGA design, validation and implementation of an Orthogonal Frequency Division Multiplexing (OFDM) transceiver for DVB-T using a high level design tool and also reports the resources requirements for the presented system.